Valsas de Francisco Mignone: transcrição e edição para violoncelo - Antonio Afonso Goncalves (2004)
The 16 valzes for bassoon solo by Francisco Mignone were written in 1979 and 1981. They are considered the first Brazilian method to the bassoon. This musical collection is known by many instrumentists around the world and considered a masterpiece. Their colourful sound is genuinely Brazilian and remember the musical youth of the composer Francisco Mignone. This research is about the transcription of the three valtzes from this collection to the cello. It presents a musical analysis of the selected valtzes, discussions about technichal aspects, bows suggestion and a special performance edition for cello of the mentioned valtzes. It presents also the historical background of the composer,some aspects of the musical transcriptions and a short historical background of the referred instruments.